Exploring How EFL Young Learners Are Being Assessed in Ghat Primary Schools - Sumaya Ramadan Aoghala; Manana Alhasen Mohamed (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This study sought to investigate how EFL young learners are assessed at some primary schools in southern Libya (Ghat) and the challenges their teachers encounter when using classroom activities as alternative assessment techniques. The study employed a mixed-method approach, in which a closed-ended questionnaire and semi-structured interviews were employed. Twenty teachers, including males and females from different schools in the area, were invited to participate in the study. The results revealed that the majority of the targeted teachers preferred traditional assessment techniques in comparison to alternative ones. Furthermore, the results also showed that some targeted teachers lack appropriate knowledge of prevailing terms in the assessment field, such as feedback and alternative assessment tools such as portfolios. Another significant finding was that the teachers faced challenges in assessing young learners during classroom activities due to individual differences, large classes and the limited time allocated for English classes, disruptive behaviours of some students, difficulty in evaluating individual contributions in group activities, and students’ anxiety and shyness to work in groups. The study suggests integrating topics about assessing language in young learners in the assessment module. Moreover, it also suggests organizing constant training sessions for teachers while at their work to enhance their knowledge of assessment, in general. Furthermore, the study also recommends more research studies on alternative assessment techniques and ratings could be conducted.